Russia's food economy in transition: what do reforms mean for the long-term outlook? - von Braun, Joachim; Seeth, Harm tho; Serova, Eugenia; Melyukhina, Olga (International Food Policy Research Institute, 1996)
Russia's food economy is undergoing a fundamental transition. Rapid changes and adjustments are still taking place in the market and pricing systems, in the subsidies to output and input markets and the credit market, and in the process of privatization and other structural reforms. These transformations have far-reaching effects on domestic supply and demand relationships. And, as part of the still greater economic changes taking place in the former planned economies of central and eastern Europe, these transformations may have extensive ramifications for international food markets. The authors describe agricultural policy before reform and then the state of reforms and agriculture today. They then turn to future food consumption and production trends. The authors conclude that Russian agriculture will remain in transition for a long time. Risky labor and food markets and the inaccessibility of financing are causing the expansion of small-scale farming and the home production of food. Managerial deficiencies and market imperfections are hindering a revitalization of large-scale farming. Certainly the potential for major production increases exists in Russia, as well as in some other countries of the former Soviet Union, especially Ukraine and Kazakhstan. One need not be overly optimistic to assume that efficiency will improve and this potential will be realized over the long term. During the period covered by the projections given here, however, institutional constraints, friction in finance, land, and labor markets, and limited infrastructure will probably prevent farmers and the food-processing sector from responding strongly to incentives and will continue to inhibit the efficiency and growth of the Russian food economy.